Pemanfaatan Manajemen Sarana Prasarana Pembelajaran di Madrasah Diniyah At-Taqwa Kecamatan Ra'as Kabupaten Sumenep - Nur Mahmudi Ismail; Hendra Purwanto; Alfan Absor Mukmin; Nur Fitriyah (Adaara: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the management of the use of facilities and infrastructure in learning, at Madrasah Diniyah At-Taqwa, Ra'as District, Sumenep Regency. This study uses a qualitative method. The subjects in this study were school principals, teachers and school committees. Data collection techniques using observation and interviews. Data analysis techniques using interactive models. Utilization of learning facilities and infrastructure through planning, implementation and control of facilities and infrastructure. The obstacles are that the place needs funds for repairs, as well as the lack of adequate facilities and infrastructure. To overcome this problem, optimizing limited personnel, namely being more observant in determining priorities or needs according to the existing budget, then involving existing personnel in formal courses or training.